N-[4-(3-methyl-3-mesityl-cyclobuty1)-thiazol-2-y1]-succinamic acid: X-ray structure, spectroscopic characterization and quantum chemical computational studies - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Elsevier, 2013)
The aim of this study is to present results of a detailed investigation of the title compound, N-[4-(3methyl-3-mesityl-cyclobuty1)-thiazol-2-yl]-succinamicacid (C21H26O3N2S). The compound was prepared in the laboratory and crystallized in the monoclinic space group P (3) over bar with a = b = 22.4066 (5) angstrom, c= 8.0744 (2) angstrom, gamma =120, and Z = 6. The molecule characterized by experimental methods such as H-1 NMR, C-13 NMR, IR and single-crystal X-ray diffraction. The molecular geometry, vibrational frequencies, gauge including atomic orbital (CIAO) H-1 and C-13 NMR chemical shift values of the title compound in the ground state was optimized quantum chemistry methods(Hartree-Fock (HF) and density functional method (OFT) (B3LYP) with 6-31G(d,p) basis set). In order to identify low energy conformation, molecular energy profile of the title molecule was obtained by semi-empirical quantum chemistry method (AM1) calculations with respect to a selected degrees of torsional freedom, which were varied from -180 degrees to +180 degrees in steps 10 degrees. In addition to the molecular electrostatic potential (MEP), frontier molecular orbital (FMO) and Mulliken population analysis of the title compound were investigated by theoretical calculation results. Published by Elsevier B.V.
Keywords: Cyclobutane; Thiazole; Hartree Fock (HF); Density functional theory (DFT); Conformational analysis; IR and NMR spectroscopy